Midwifery Care for Pregnant Women Mrs. M G:l P:0 A:0 With Emesis Gravidarum Using Ginger Aromatherapy in Independent Practice Bd Elfi syahri Sirait S.Tr.Keb Kec Sei Kepayang Kab.Asahan - Iklima, Suci; Andriani, Fitri (Institute of Accounting Research and Novation (IARN), 2023)
Pregnancy changes the body, both physically and mentally. This results in complaints such as nausea, vomiting / emesis gravidarum. Emesis is a normal or common symptom during the first trimester of pregnancy. This sometimes occurs in the morning, but can also occur during the day or night. Complementary therapy to overcome complaints of emesis gravidarum with ginger aromatherapy. This study aims to determine the effect of Ginger Aromatherapy on Reducing Emesis Gravidarum in Pregnant Women in the First Trimester with midwifery care using the 7-step Varney approach. This study uses an Experimental method with 7 Varney steps where data assessment, data interpretation, potential diagnosis, needs and immediate action, planning and implementation. The study population was all primigravida in the first trimester of Primigravida in the Bd Elfi Syahri Sirait clinic area, Sei Kepayang district. The sample in this study showed that there was a significant effect of giving ginger aromatherapy on Reducing Emesis Gravidarum in Pregnant Women in Trimester I. Ginger aromatherapy has the ability to control nausea and vomiting in the body and helps relax various systems in the body. Ginger aromatherapy can be an alternative to overcome emesis gravidarum in pregnant women in the first trimester.